The role of economic growth in containing inflationary spiral in selected ASEAN countries: Panel data evidence from Malaysia, Indonesia, Thailand, and Singapore - Ahmad Ridwan Ahmad Radzi; Abdul Razak Abdul Hadi (Contemporary Economics, 2023)
This paper aims to investigate the effect of the gross domestic product growth rate on inflation in these four selected ASEAN countries. This study is worthy as there is a need to understand the variance of national inflation for these ASEAN countries, particularly when Singapore's inflation rate is the lowest among them. The Keynesian Theory and Static Panel Data analysis are put to the test in this empirical study. The investigation is carried out on yearly balanced panel data involving four ASEAN member countries. The secondary data is extracted from the World Bank database over a study period of sixty years from 1961 to 2020. The methodology is based on static panel data analysis involving both Fixed Effect and Random Effect models. The empirical results show that there is a negative significant relationship between economic growth and inflation within the four countries sampled. As such, the policy implication from this study may suggest that it is important for ASEAN-4 governments to continue beefing up their economic growth in order to curb inflationary pressure.
Keywords: G15; F10; 330; inflation; ASEAN; fixed effect; random effect; static panel data